2007
DOI: 10.1007/s11665-007-9151-y
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Reactions in Reflowed and Aged Sn-58Bi BGA Packages with Au/Ni/Cu Pads

Abstract: The reflow of Sn-58Bi solder joints in a BGA package with Au/Ni/Cu pads has been performed by employing various temperature profiles, which results in the formation of (Au 0.66

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The appearance of Ni 3 Sn 4 intermetallic phase at the interfaces of Ni electroplated pads with Sn-58Bi and Sn-58Bi-0.5La solders is consistent with previous results for the interfacial reactions between Sn-58Bi solders and Ni substrates [10][11][12][13]. However, the (Au 0.3 Ni 0.7 )(Sn 0.9 Bi 0.1 ) 4 /Ni 3 Sn 4 double layers as reported by Chi et al [14] at the interfaces of Sn-58Bi solder joints with Au(0.5 m)/Ni(5 m)/Cu pads were not found in the present study. The absence of a (Au 0.3 Ni 0.7 )(Sn 0.9 Bi 0.1 ) 4 intermetallic layer on the Ni 3 Sn 4 phase is attributed to the very thin Au film (0.1 m) on the Ni/Cu pads.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…The appearance of Ni 3 Sn 4 intermetallic phase at the interfaces of Ni electroplated pads with Sn-58Bi and Sn-58Bi-0.5La solders is consistent with previous results for the interfacial reactions between Sn-58Bi solders and Ni substrates [10][11][12][13]. However, the (Au 0.3 Ni 0.7 )(Sn 0.9 Bi 0.1 ) 4 /Ni 3 Sn 4 double layers as reported by Chi et al [14] at the interfaces of Sn-58Bi solder joints with Au(0.5 m)/Ni(5 m)/Cu pads were not found in the present study. The absence of a (Au 0.3 Ni 0.7 )(Sn 0.9 Bi 0.1 ) 4 intermetallic layer on the Ni 3 Sn 4 phase is attributed to the very thin Au film (0.1 m) on the Ni/Cu pads.…”
Section: Methodssupporting
confidence: 92%
“…The intermetallic phases after interfacial reactions between Sn-58Bi solders and Ni substrates have been analyzed by many researchers [10][11][12][13][14]. Chen et al studied the thermal aging of Sn-58Bi solder joints at 85, 100 and 120 • C, and reported that a Ni 3 Sn 4 intermetallic phase formed at the interface [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDS analysis identified that the chemical composition of the new IMC was approximately 65.35 at.% Sn, 15.95 at.% Bi, 9.20 at.% Ni, and 9.50 at.% Au, corresponding to (Au,Ni)(Sn,Bi) 4 phase. [23][24][25] These IMCs grew with increasing aging time. In the case of the ENEPIG surface finish, the dissolved Au formed Sn-Au-Pd IMCs that precipitated out of the solder during solidification and formed flake-shaped IMCs during reflow.…”
Section: Methodsmentioning
confidence: 97%
“…Currently, the developed low-temperature solders are mainly selected from the Sn-Bi, Sn-In or Sn-Zn series [4]; but Sn-Bi solder provides the most potential due to its low cost and better comprehensive properties [5].The Sn-Bi binary solder system can reach the low eutectic temperature at 138 • C with a composition of Sn-58Bi, which provides the ideal processing temperature. However, there still exists some serious concerns on the application of Sn-58Bi eutectic solder, such as the interfacial embrittlement in solder joints [6][7][8][9], poorer drop reliability [10], the deterioration on joint strength after aging service [11], etc. All these problems are mainly attributed to the inherent embrittlement of Bi atoms.…”
mentioning
confidence: 99%